Transmedia narratives in digital enviroments: "Inanimate Alice" as a hypermedia novel and its educational purposes - Abril Hernández, Ana (CIC. Cuadernos de Información y Comunicación, 2014)
The new means of interacting with our environment are more conditioned every day due to the spread use of new technologies as a source of knowledge acquisition and transmission. This article analyzes the level of participantengagement in one of the first digital novels used for pedagogical purposes worldwide: Inanimate Alice . This work of digital literature contains a direct reference that establishes a connection to the outer educational environment where it is used. This novel is also a transmedia work as it combines various communication platforms and mixes different artistic genres: it is a digital novel but also a PC game. Inanimate Alice presents a story with an invisible narrator in the images and with very few possibilities of actual manipulation of the novelgame. Therefore, this study follows a sociosemiotic approach of the hypermedia elements of this novel with the purpose of suggesting possible modifications and thus, enhance the interactive and interpersonal engagement of the series.
Keywords: transmedia narrative; Inanimate Alice; hypermedia novel; metafiction; digital pedagogic resource.